THE CONCENTRATION OF HEAVY METALS Pb, Cu and Zn IN OLIVE RIDLEY SEA TURTLE’S EGG (Lepidochelys olivacea) IN SPAWNING LOCATIONS OF PARIAMAN TOWN BEACH WEST SUMATRA PROVINCE - Shintana, Mayang; Nedi, Syahril; Tanjung, Afrizal (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research was conducted in June 2015 with the aim was to knowing the concentration of heavy metals of Pb, Cu and Zn accumulated in the albumen and yolk of olive ridley sea turtle (Lepidochelys olivacea) from Pariaman town beach, West Sumatra Province. The method used was a survey conducted on 3 beaches. The results showed that the average metal Pb in albumen (2.7644 μg/g) was greater than the metal Cu (2.0970 μg/g) and smaller than the metal Zn (10.4924 μg/g). While metal Pb in yolk (6.8008 μg/g) was smaller than the metal Cu (7.0357 μg/g) and metal Zn (34.1479 μg/g). The PTWI calculation value (the Provisional Torelable Weekly Intake) based on FAO/WHO standard for an adult weighing of 70 kg told that the eggs were still reasonably consumtable as long as it did not exceed the limit of 3.2932 kg/week for Pb, 482.8780 kg/week for Cu and 197.5793 kg/week for Zn. However, consumsing turtle eggs continuously can harm the body’s health and threaten the sustainability of turtles in the wild. Key words: Heavy metals, turtle eggs, Olive Ridley sea turtles (Lepidochelys olivacea), Pariaman Beach